1997
DOI: 10.1037/0096-1523.23.2.504
|View full text |Cite
|
Sign up to set email alerts
|

Personal names and the attentional blink: A visual "cocktail party" effect.

Abstract: Four experiments were carried out to investigate an early- versus late-selection explanation for the attentional blink (AB). In both Experiments 1 and 2, 3 groups of participants were required to identify a noun (Experiment 1) or a name (Experiment 2) target (experimental conditions) and then to identify the presence or absence of a 2nd target (probe), which was their own name, another name, or a specified noun from among a noun distractor stream (Experiment 1) or a name distractor stream (Experiment 2). The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
224
4
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(257 citation statements)
references
References 20 publications
24
224
4
3
Order By: Relevance
“…For instance, it has been shown that self-referential stimuli elicited specific effects when their processing was somehow related with the task at hand (Brédart et al, 2006;Gronau et al, 2003;Kawahara & Yamada, 2004;Shapiro et al, 1997) but not when their processing was totally irrelevant for the task and when they never shared relevant properties with the target items (e.g. Bundesen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been shown that self-referential stimuli elicited specific effects when their processing was somehow related with the task at hand (Brédart et al, 2006;Gronau et al, 2003;Kawahara & Yamada, 2004;Shapiro et al, 1997) but not when their processing was totally irrelevant for the task and when they never shared relevant properties with the target items (e.g. Bundesen et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the fact that the to-be-ignored stimuli were presented at fixation, they were located within the focus of attention and were presumably attended, preventing any strong conclusion in favour of a late selection theory of attention. Subsequently, other studies demonstrated that one's own name is particularly resistant to the attentional blink (Shapiro, Caldwell, & Sorensen, 1997) and to repetition blindness (Arnell, Shapiro, & Sorensen, 1999) during rapid serial visual presentations when compared to other names or nouns. In the inattentional blindness paradigm, the own name is also less subject to blindness than other names or frequent words (Mack & Rock, 1998).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, familiar or meaningful stimuli, such as one's own name (Shapiro, Caldwell, & Sorensen, 1997) or famous faces (Jackson & Raymond, 2006) are protected to some degree from the AB as their identification is less impaired than similar but less familiar stimuli. Smith, Most, Newsome, and Zald (2006) also showed that a stimulus recently associated with an aversive burst of white noise can automatically induce an AB-like impairment when used as a distractor in an RSVP task.…”
Section: The Attentional Blinkmentioning
confidence: 99%
“…For instance, in a visual analogy of the Moray's procedure, Wolford and Morrison (1980) showed that when instructed to make a parity judgment on two digits flanking a to-be-ignored word, a higher proportion of participants subsequently reported that they had seen their own name in comparison with words presented the same number of times during the experiment. Shapiro's team later showed that the own name is particularly resistant to the attentional blink (Shapiro, Caldwell, & Sorensen, 1997) and to repetition blindness (Arnell, Shapiro, & Sorensen, 1999). In addition, Mack and Rock (1998) found that almost all of their participants (88%) detected their own name when presented under conditions of inattention in the inattentional blindness paradigm.…”
Section: Introductionmentioning
confidence: 99%